Comparison of NK cell subsets, receptors and functions induced by radiofrequency ablation and microwave ablation in HBV-associated primary hepatocellular carcinoma - Wang, Hai-Yan; Cui, Xiong-Wei; Zhang, Yong-Hong; Chen, Yu; Lu, Ning-Ning; Sheng, Shou-Peng; Gao, Wen-Feng; Yang, Xiao-Zheng; Duan, Zhong-Ping (Frontiers in Oncology, 2023)
Background Topical therapy has been shown to induce an immune response in patients with hepatocellular carcinoma (HCC). In this study, a prospective parallel group control experiment was conducted to compare the differences between radiofrequency ablation and microwave ablation in inducing the immune regulation of NK cells. Methods Sixty patients with clinically and pathologically confirmed hepatitis B-associated hepatocellular carcinoma (HCC) were selected for thermal ablation. Patients were randomly assigned into the MWA group (n = 30) and the RFA group (n = 30). Patient’s peripheral blood was isolated on days D0, D7, and month M1. NK cell subsets, receptors, and killing function were detected by flow cytometry and LDH. Student t test and rank sum test were used to compare the statistical differences between the RFA (radio frequency) and MWA (microwave) groups. The Kaplan-Meier curve and log-rank test were used to calculate the difference between the two survival curves. Results Comparison of the frequency of CD3-CD56+ and CD3-CD56+CD16+ in NK cells between the RFA and WMA groups showed that there was no difference in the D0, D7, M1, D7-D0, M1-D0, and M1-D7 groups. The changes of the inhibitory NK cell receptor CD159A were significantly different at D7 (P<0.05). CD107a were compared between the RFA and WMA groups, indicating that CD107a changes induced by NK cells were significantly different at D7-D0 (P<0.05). Comparison of NK cell lysis activity of target K562 cells between the RFA and WMA groups showed that there was no difference at D0, D7, D7-D0. There was no difference in recurrence-free survival (RFS) between the RFA and WMA groups (P=0.11). Conclusions The difference between MWA and RFA-induced NK cell changes was mainly manifested in the inhibitory receptors CD159a and CD107a 1 week after surgery, with microwave-induced changes being more severe. Comparison of the NK cell lysis activity of the target K562 cells between the RFA and WMA groups showed that there was no difference in D0, D7, D7- D0. Survival analysis showed that these differences did not affect the recurrence-free survival (RFS) in the two groups.